PENGARUH INDOMARET TERHADAP EKSISTENSI TOKO KELONTONG DI JALAN DELIMA KECAMATAN TAMPAN KOTA PEKANBARU - Kartika, Mela; Kartikowati, Sri; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : This research was conducted at the Grocery Store located at Delima Street Tampan District of Pekanbaru City. Sources of data from informants and Indomaret respondents and Grocery Stores. Data collection techniques derived from structured interviews, questionnaires, observation and documentation. Engineering Data analysis was performed after the data collected from the respondents who had been interviewed and given questionnaires. The method used is descriptive analysis, historical analysis and survey. Data analysis techniques using primary data and secondary data. The results of the study all these indicators affect the income of the grocery store. There is a grocery store merchant income changes after Indomaret. This situation looks from the grocery store merchants Declining revenues due to the decline in the number of consumers and the sale of goods. The existence Indomaret in Delima Street impact on merchants grocery store that is seen from working capital, long opening hours, sales turnover, number of customers and the amount of revenue decreases and declined after the Indomaret. Of reduction and a decrease in these indicators will impact on the existence of a grocery store in Delima street.Keyword : Effect, indomaret, grocery store